The socialization of preadolescents in family holidays: A serial mediation model. (December 2022) - Xu, Wenqing; Li, Mimi; Lin, Guyang; Feng, Xiaohong
Abstract: This study considers preadolescents' impacts on their family's holiday decisions by framing the socialization process as dynamic. Links in this process result from the performative effects of preadolescents' age, family communication patterns, level of tourism knowledge, and perceived tourism importance. Specifically, a serial mediation model based on consumer socialization theory was devised to examine the proposed relationships; 704 preadolescents from Southeast China participated. The findings suggest that preadolescents' age positively contributes to their impacts on family holiday decisions. Furthermore, mediating roles of family communication patterns and perceived tourism importance were found statistically significant. Findings offer a deeper understanding of preadolescents' learning mechanisms as consumers in family tourism. These results can inspire further discussion of temporal and contextual variability in the association between family tourism and preadolescents' socialization. Graphical abstract: Image 1